Translation as a Form of Literary Communication in Poetry of Silver Age: Three Lyrical Versions of a Poem by Paul Fort - A. A. Ustinovskaya (Научный диалог)
Three translations of Paul Fort small poem “Cette fille, elle est morte” by Konstantin Balmont, Valery Bryusov and Mikhail Kuzmin are considered. The results of a comparative analysis of these three texts using the analysis of the original are presented. The question is raised about the originality of the form used by Paul Fort: the text he wrote is a deformed trio, and this deformation should be recognizable for his potential reader. It is stated that the semantic side of the text is ambivalent: in the first half of the text negative moods prevail, in the second - positive ones, which is shown not only lexically, but also rhythmically. The relevance of the study is due to a detailed analysis of the three translations using material about the biography and work of the translators  themselves. The novelty of the research is seen in the fact that such an analysis of the translation options for the Fort text and its formal, rhythmic and sound features has not been carried out before. The author dwells on the characteristic features of each of the three translations, noting both their connection with the original and the reliance on the translation of the predecessor, or, on the contrary, ignoring it. Particular attention is paid to the grammatical and lexical features of the original, which allow for an ambivalent interpretation of the meaning of the text.